Implementasi kebijakan pengawasan kearsipan internal pada Badan Meteorologi, Klimatologi, dan Geofisika (BMKG) - Yulia Nurul Aini; Bambang Giyanto; R. Luki Karunia; Marlina Nababan (Universitas Merdeka Malang, 2024)
Archives are records of activities and events made and received by an agency that are useful as a monitoring tool and source of information. To protect the archives, archival supervision activities are carried out in accordance with PerANRI No. 6/2019 concerning Archival Supervision. BMKG is one of the LPNKs that has carried out internal archival supervision activities since 2019. The implementation of internal archival supervision at BMKG needs to be carried out to keep Meteorology, Climatology and Geophysics data and administrative data well managed and maintained. Using the policy implementation theory model from Van Horn, Van Meter, and Grindle which includes policy standards and objectives, resources, inter-organizational relationships, attitudes, characteristics of implementing agents, social and political conditions, and types of benefits. Using qualitative research with a descriptive approach. The results showed that the implementation of the internal archival supervision policy still has limited archival human resources and financial resources, and not all work units have carried out archival supervision so that MKG observation data has not been saved. Some of the inhibiting factors are inadequate human resources, limited funds, and a work culture that is less concerned about archives.